GC-MS-based metabolomics analysis unravels the therapeutic potential of Neolamarckia cadamba fruit peel - Selvakumar, Divya; Vaikuntavasan, Paranidharan; Sampathrajan, Vellaikumar; Manoharan, Bharani; Adhimoolam, Karthikeyan; Nallusamy, Saranya; Arunachala, Balasubramanian; Senthil, Kalaiselvi; Natesan, Senthil (Journal of Phytology, 2022)
Kadam (Neolamarckia cadamba (Roxb.) is an evergreen tropical tree widely grown in Asia, particularly in India. Neolamarckia cadamba commonly known as kadam, cadamba or burflower tree. The roots, leaves, barks, and fruits of N. cadamba possess medicinal properties and are commonly used in the pharmaceutical industry. Fruit peels are the main waste and may contain various biologically active compounds. However, no prior knowledge about the therapeutic compounds of the peel. The objective of the present study was to unveil therapeutic compounds from the peel by Gas Chromatography–Mass Spectrometry (GC-MS) based metabolomics analysis. Metabolites from the kadam fruit peel were isolated and derivatized using MSTFA, characterized by the GC-MS analysis. Raw spectral data were pre-processed, and peak identification was performed using SHIMADZU Postrun analyse software. The metabolites in N. cadamba fruit peel were identified by comparing the peaks with the mass spectral reference database NIST v20. The results showed that the peel of kadam fruit contains 149 metabolites, which were further categorized into 46 different metabolite classes, with 52 different metabolic pathways and 63 biological functions. The principal roles of the metabolites were identified by functional annotation and enrichment analysis. It revealed that metabolites were responsible for anti-inflammation, anti-oxidant, anti-microbial, and anti-cancer properties. In summary, the peel of kadam fruit also contains various therapeutic compounds like other cadamba parts (i.e., roots, leaves, barks, and fruits). Further, comparing the peel with other parts discloses the peel-specific metabolites. The results obtained in this study could be useful for the pharmaceutical industry.